A landscape architect preferences on border elements at green open spaces during Covid-19 pandemic - Dian Kartika Santoso; Irawan Setyabudi (ARTEKS : Jurnal Teknik Arsitektur, 2021)
Green open space has many benefits for humans. Unfortunately, the function of green open space cannot be fully felt due to the Covid-19 pandemic. Even though the application of physical distancing in the garden can be created through the use of garden border elements. As a first step in determining good and effective elements, this study aims to explore the preferences of garden designers in selecting garden border elements, their shapes, and arrangements to maintain the distance between garden users. This research is a perceptual research using a survey method obtained through distributing questionnaires and processed by quantitative descriptive and chi-square test. As for the results obtained in this study, garden designers agree that the border element is an effective way that can be used to implement physical distancing in public parks. Although, in general, garden designers prefer hardscape over softscapes as a border element, there are different preferences for the type of hardscape and softscape used. Garden designers prefer fences, portable benches> 2m apart and concrete construction as a hardscape barrier that can be applied to gardens that have been built. Meanwhile, the selection of softscape in the garden that has been built tends to use flowering shrubs as a border element. The conclusion of this study is the preference for material selection that is different in terms of functionality and aesthetics is caused by the pandemic